Artificial intelligence: how can Gen-AI tools support the current business models of the firms and add value? - Scappaticci, Chiara Silveira (2023)
Amid the digitalization era, this thesis explores the transformational impact of Generative Artificial Intelligence (Gen-AI) on business models to support firms in creating a cohesive digital strategy utilizing Gen-AI solutions by answering the research question: how can Gen-AI tools support the current business models of the firms and add value? The study starts by defining digital transformation and its significance. Then, it explores AI’s historical evolution and its role in driving digital transformation. Finally, the thesis also elaborates on Gen-AI, emphasizing its tools, current business applications, and potential to drive digital transformation in organizations in the upcoming years. Moreover, by interviewing industry experts to explore existing business strategies and utilizing the Business Model Canvas framework, the thesis identifies areas within firms that Gen-AI can impact. The interviews provided valuable insights into various business strategies, revealing how the areas can be impacted by Gen-AI and the potential tools that firms can adopt. Additionally, experts also collaborated by providing market trends that their firms are investing in. The key findings challenge the traditional view of Gen-AI as just a supportive tool. Instead, the experts explore the Gen-AI capacity to reinforce or redefine a firm’s value proposition and improve its cost structure. The study also provides emerging trends, such as the one-person enterprise, which can be a redefining concept for business in the future. To conclude, this thesis underscores the potential impact that Gen-AI can have on business models. It contributes by presenting practical insights for businesses to benefit from the usage of Gen-AI while emphasizing responsible and ethical deployment. Overall, the research highlights Gen-AI as one of the main drivers of impact in the digital transformation landscape.